2012
DOI: 10.1267/ahc.11041
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Protein Phosphatase 1δ with Nucleophosmin in Human Osteoblastic Cells

Abstract: Protein phosphorylation and dephosphorylation has been recognized as an essential mechanism in the regulation of cellular metabolism and function in various tissues. Serine and threonine protein phosphatases (PP) are divided into four categories: PP1, PP2A, PP2B, and PP2C. At least four isoforms of PP1 catalytic subunit in rat, PP1α, PP1γ1, PP1γ2, and PP1δ, were isolated. In the present study, we examined the localization and expression of PP1δ in human osteoblastic Saos-2 cells. Anti-PP1δ antibody recognized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…We previously reported that OA induced apoptosis in human osteoblastic cells (2729). Protein kinases and phosphatases were reported to be involved in transcriptional stimulation through activation of the NF-κB pathway (15,30). We reported that the PKR/eIF-2α pathway was activated and that NF-κB translocation occurred during the OA-induced apoptosis (7,31).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that OA induced apoptosis in human osteoblastic cells (2729). Protein kinases and phosphatases were reported to be involved in transcriptional stimulation through activation of the NF-κB pathway (15,30). We reported that the PKR/eIF-2α pathway was activated and that NF-κB translocation occurred during the OA-induced apoptosis (7,31).…”
Section: Introductionmentioning
confidence: 99%
“…Immunoprecipitation was performed as described previously [33], using specific antibodies for IRF4 and IRF8.…”
Section: Methodsmentioning
confidence: 99%